UMP products win Malaysia Commercialisation Year 2020 (MCY 2020) Award - Mimi Rabita, Abdul Wahit (2020)
KUALA LUMPUR, 17 December 2020 – Universiti Malaysia Pahang (UMP) continues to record success in commercialisation, with two products developed by UMP receiving the Malaysia Commercialisation Year 2020 (MCY 2020) awards.